A história em tempos de crise: Friedrich Meinecke (1862-1954) e os problemas do historicismo alemão - Cunha, Marcelo Durão Rodrigues da (2017)
This thesis aims to provide a new interpretation of the crisis experienced by the German historical consciousness between the end of the nineteenth century and the conclusion of World War II. Interpreted by many as a so-called “crisis of historicism”, our thesis suggests that the crisis was not experienced only by German academics and intellectuals, but also impacted the broader historical conception sustained by European man since the rise of modern experience in the West. It will be suggested that in the discussions of German intellectuals from the second part of the nineteenth century onwards about the meanings of history and of historicism, it is possible to identify a debate about the epistemologic limits of the historical discipline as well as a farreaching discussion about the bounds inherent in the concept of history—conceived as a "collective singular"—in modern times. To demonstrate this hypothesis, an examination will be made of the work and life trajectories of some intellectuals who were directly involved in the struggles about the problems of historicism, and who were concerned with the meaning of history—in terms of religion and of belief in the modern nation state—after the collapse of trust in that absolute historical conception during the period of crisis. A discussion—developed in our first two chapters—will allow us to set up a new interpretation of the work of the historian Friedrich Meinecke. His life trajectory is central not only to the understanding of the process of dissolution of the modern concept of history, but also to acknowledging how part of German historiography reacted to this crisis. Finally, it will be sustained that all of Meinecke’s work as a historian—with a special emphasis on this concept of historicism—consisted of an attempt to provide answers and to overcome the historical crisis experienced in Germany in the latter nineteenth and early twentieth century